Less conservative state feedback design conditions for switched takagi-sugeno fuzzy systems - Faria, Flavio A. [UNESP]; Elias, Leandro J.; Araujo, Rayza; Oliveira, Vilma A. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Relaxed conditions for switched Takagi-Sugeno fuzzy systems under state feedback are proposed. The result explores two strategies to decrease the linear matrix inequalities (LMIs) conservatism. Properties of membership are explored to add slack matrix variables into the LMI formulation and a standard right hand side LMI relaxation procedure is extended for switched TS fuzzy systems. Numerical examples illustrate the efficiency of the presented results.